The multidisciplinary approach of a patient with Sjögrenś Syndrome in the dental office - case report - Coman Tatiana-Maria; Mănărăzan Anca-Diana; Cîrstea Adelin-Sebastian; Cocoș Dorin-Ioan ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2019)
Introduction: Oral rehabilitation is based on establishing a correct diagnosis and designing a plan to give appropriate treatment to each clinical case. Patients' aesthetic requirements show an increasing trend in current practice. Sjögren's syndrome and obesity can have a negative impact on a person's quality of life, and it is therefore imperative to identify and reduce these significant barriers to paving the way for better oral health and the overall well-being of the individual. Hypertension NYHA II type patients may present oral manifestations like ageusia, burning sensation, xerostomia, lichenoid reactions or gingival hyperplasia. Case presentation: This time, at our clinic, a 71-year-old man requested a complex oral rehabilitation. He presented partial edentulism at both arches. We are talking about a non-smoking patient, with chronical medication treatment for the mentioned pathology. Conclusions: A well-controlled hypertensive patient is not a risk in clinical practice. When choosing an implant based therapy, the old age of the patient can be considered a negative factor for successful results, but it is not a strict contraindication. This case report shows the most suitable treatment solution, regarding all the advantages and disadvantages of other treatment options, represented by implant supported fixed prosthetic restaurations.